Infrared spectra of the electronic superconductors Nd2−xCexCuO4 - Lavat, Araceli Elisabet (1991)
Tokura et al. have recently discovered a new class of superconducting materials derived from NdzCuO4, substituting a part of the Nd(III) by Ce(IV) and generating phases of composition Ndz_xCexCuO 4. These materials become n-type (electron-doped) superconductors by contrast to previously studied high-To superconductors which are p-type (holesdoped) materials. The n-type character has been confirmed by Hall and Seebek measurements, whereas X-ray absorption studies and photoelectron spectroscopy indicate the presence of Cu(I).